A Socio-Pragmatic Study of Politeness Strategies and Social Contexts in Joker Movie - Asheva, Alhabiib Josy; Santosa, Riyadi (Jurnal Bahasa, Sastra, dan Studi Amerika, 2022)
This research targets a holistic investigation of the types of politeness strategies performed by the characters in Joker movie along with their social contexts. It further aims to find the influences of movie stages (orientation, complication, evaluation, resolution) and social factors (power, social distance) to the use of politeness strategies by the characters of the movie. This study utilized a socio-pragmatics approach to investigate the social contexts and a theoretical framework proposed by Brown and Levinson (1978) to identify politeness strategies in the movie. This research was upheld using descriptive qualitative research which is underpinned by four major stages of analysis by Santosa’s (2021) model, in combination with Spreadly (1980), and Miles and Huberman (1996) ranging from domain, taxonomy, componential, and cultural theme analysis. The data of this research are taken from the dialogues that contained politeness strategies performed by the characters. The data sources come from the stages of Joker movie ranging from the orientation, complication, evaluation, and resolution.